(untitled) (Research, Society and Development, 2021)
The pandemic of the new coronavirus brought the challenge of remote education to education. Schools are adapting their actions to meet this unusual form of teaching in their daily lives. In this context, the question arises as to how the inclusion of students with disabilities in this type of teaching is being carried out. Thus, this article aimed to analyze the inclusion of students with disabilities during the New Coronavirus Pandemic period in the scope of Basic Education. An exploratory research with a qualitative approach was used, using a semi-structured questionnaire as an instrument. The research subjects were 52 teachers enrolled in the Graduate Program in Teaching, with an emphasis on basic education and inclusive education, at the IFMG campus Arcos. It was observed in the research that, in the perception of teachers, a large part of students with disabilities are out of an educational context at this time. Among the reasons for these students not being accompanied by the school or accompanied in a precarious way are the lack of access to technology; difficulty in monitoring by the family and / or guardian and activities not adapted for students with disabilities. It is concluded that the Pandemic of the new Coronavirus worsened the scenario of school exclusion for students with disabilities.